Access to Justice Due to the Covid-19 Pandemic - Golubeva, Nelli; But, Illia; Prokhorov, Pavlo (Ius Humani. Jornal do direito, 2020)
The coronavirus pandemic (Covid-19) has caused many challenges to democracy around the world. Under the new conditions, states must implement effective quarantine measures, as well as take decisions that justifiably and least restrict human rights. In this pandemic context of many restrictions, it is important to pay attention to ensuring access to justice and to investigate its level of security. The article aims to analyze the right of access to justice in the context of the Covid-19 pandemic, both in Ukraine and other countries. The subject of the study is the public relations that arise during the exercise of the right of access to justice in the pandemic context. The research methodology includes a scope of methods, the most important of which are the dialectical method, the analysis method, the synthesis method, the comparative method, the induction method, and the deduction method. As a result of the study, an analysis of the right of access to justice in the context of Covid-19 has been made. The main conclusion of this study is that the Covid-19 pandemic has clearly shown that the transition to online technology and other innovations in the judiciary has so far been too slow. On the other hand, in the context of ensuring access to justice the pandemic has become a kind of trigger for the rapid development and implementation of the latest innovative technologies in the field of access to justice.